BACKGROUND TO CONDUCT AND COMPLEX PROBLEMS NEW REGIONAL POLICY IN UKRAINE - Zakharchenko , V.I. (The actual problems of regional economy development, 2019)
The article shows that the implementation of a new regional policy in Ukraine, based on the paradigm of the new regionalism, runs into considerable difficulties, in which significant role belongs to scientific development. It is found that in most of them insufficient attention is paid to assessing the prerequisites for a new regional policy in Ukraine and to systematize and analyze its main problems that need to be addressed in the current period. It is aimed at conducting a special study of the preconditions and complex problems of the new regional policy in Ukraine. The study used general scientific (analysis and synthesis, logical generalization, comparative) and economic and statistical (absolute, relative and average values, index, rating and grouping) methods. The background of the new regional policy in Ukraine related to the Russian aggression, intensification of the processes of globalization and regionalization, aggravation of contradictions between regions are analyzed. In this connection, the necessity of isolating and solving such complex problems of the new regional policy as: political and economic disintegration of the Ukrainian regions is argued; deepening asymmetry in the socio-economic development of regions; polarization of economic space; unpreparedness of regions to face the challenges of globalization; low level of regional competitiveness and, accordingly, regional human development. The article proposes measures to solve these problems, which are based not only on direct assistance to the center of the regions, but also provide incentives for efficient use of their resource potential, activation of innovation and investment activity and enhancement of the international competitiveness of regions in the context of globalization. It is concluded that the implementation of these measures should ensure a high level of human development in all regions of Ukraine.